2014
DOI: 10.1021/ie403623f
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-lactic acid)-block-poly(butylene succinate-co-butylene adipate) Multiblock Copolymers: From Synthesis to Thermo-Mechanical Properties

Abstract: Multiblock copolymers poly(l-lactic acid)-block-poly(butylene succinate-co-butylene adipate)s (abbr. P(LLA-mb-BSA)s) are synthesized via a polycondensation/chain extension/coupling method using binary chain extenders. A poly(l-lactic acid) (PLLA) prepolymer synthesized via direct melt polycondensation of l-lactic acid is rapidly chain extended with a bis (2-oxazoline) to form hydroxyl terminated dimer, and the dimer is then chain extended/coupled with a hydroxyl terminated poly(butylene succinate-co-butylene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…With increasing the composition of HDA in PLH copolymers, the elongation at break increased significantly. When nLA/nHDA was 5.0/1, the elongation reached 640%, which was higher than the other reported copolymers, such as the elongation at break of the modified PLLA by TFC being 12.9% [20], penta-block copolymers (penta-sb-PLA) being 470% [34], poly(L-lactic acid) and poly(butylene carbonate) (PLA-b-PBC) being 430% [35] and poly(L-lactic acid)-block-poly(butylene succinate-co-butylene adipate) (PLLA-b-P(BS-co-BA) being 503% [36]. This result suggested that the PLH copolymers had high ductility.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…With increasing the composition of HDA in PLH copolymers, the elongation at break increased significantly. When nLA/nHDA was 5.0/1, the elongation reached 640%, which was higher than the other reported copolymers, such as the elongation at break of the modified PLLA by TFC being 12.9% [20], penta-block copolymers (penta-sb-PLA) being 470% [34], poly(L-lactic acid) and poly(butylene carbonate) (PLA-b-PBC) being 430% [35] and poly(L-lactic acid)-block-poly(butylene succinate-co-butylene adipate) (PLLA-b-P(BS-co-BA) being 503% [36]. This result suggested that the PLH copolymers had high ductility.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Many approaches have been carried out to improve the toughness of PLLA including copolymerization, plasticization and physical blending. However, the synthesis of copolymers is usually complex and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…P(LLA‐mb‐BSA) multi‐block copolymers were synthesized via chain extension and coupling of poly(L‐lactic acid) (PLLA) and poly(butylene succinate ‐co‐ adipate) (PBSA, BA unit 60 mol %) prepolymers using 1,4‐PBO and HDI as chain extenders, as previously reported . The PLLA and PBSA prepolymers were synthesized via direct polycondensation and their hydroxyl values and number‐average molecular weights ( M n , determined by 1 H NMR) were 6.84 and 44.0 mg KOH/g, 8200 and 3100 g/mol, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Biodegradable polyurethane thermoplastic elastomers (TPUs) are also excellent impact modifiers for PLLA due to the flexible chain nature and the formation of hydrogen bonding between TPU and PLLA . In addition, block or multi‐block copolymers including PLLA hard segment and various soft segments including poly(ɛ‐caprolactone ‐co‐ δ‐valerolactone), poly( ɛ ‐decalactone), poly(ɛ‐caprolactone), and poly(butylene succinate ‐co‐ adipate) exhibit good to excellent composition‐depending toughness and/or elasticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation